Islamic Republic of Afghanistan : Staff-Monitored Program. (IMF Staff Country Reports; Country Report, 2015)
This paper discusses the main features of the Staff-Monitored Program (SMP) for Afghanistan. The SMP is designed to support the authorities' reform agenda with a framework to address economic vulnerabilities and facilitate engagement with the international community to sustain donor support. The SMP will foster continued close engagement with Afghanistan, address immediate fiscal and banking vulnerabilities, and help manage risks. The SMP will also preserve buffers, maintain low inflation and competitiveness, and lay the basis for high and inclusive growth. Under the SMP, fiscal policy will focus on mobilizing domestic budget revenue to finance projected expenditure and rebuild the treasury's cash balance.